Exploring the Socio-Cultural Effects of Youth Migration in Rural Areas - Basnet, Pramila; Khatiwada, Shambhu Prasad (The Third Pole: Journal of Geography Education, 2025)
This study explores the socio-cultural impacts of youth migration on the Tamang community in Dobhan village, Kakani Rural Municipality, Nuwakot district. Migration is the voluntary movement of people to change their residence, often driven by factors such as conflict, persecution, or natural disasters. Guided by conflict theory, this study analyzes migration as a process influenced by structural inequalities, resource struggles, and societal power relations, rather than a personal choice. Using qualitative methods including in-depth interviews and observations with family members of migrant youths’ data were collected. The findings reveal that migration has both positive and negative effects on the Tamang community. While migration provides economic benefits, through remittance, it also contributes to family fragmentation, emotional detachment, and erosion of cultural values. The community is experiencing new forms of stress and conflicts because of these socio-cultural power relationships. This study further concludes that many Tamang youths are seeking migration in response to climate change, land degradation, limited local employment opportunities and better income sources. These sources are complemented by foreign employment, urban migration, and livelihood diversifications. In this context, this study explores the intricate nature of youth migration in rural areas, emphasizing the need for local coordinated efforts for opportunity creation, cultural preservation, and community empowerment.